2020
DOI: 10.1093/mnras/staa977
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of kinetic plasma waves on ion-to-electron mass ratio and light-to-Alfvén speed ratio

Abstract: The magnetization |Ω e |/ω e is an important parameter in plasma astrophysics, where Ω e and ω e are the electron gyro-frequency and electron plasma frequency, respectively. It only depends on the mass ratio m i /m e and the light-to-Alfvén speed ratio c/v Ai , where m i (m e ) is the ion (electron) mass, c is the speed of light, and v Ai is the ion Alfvén speed. Nonlinear numerical plasma models such as particle-in-cell simulations must often assume unrealistic values for m i /m e and for c/v Ai . Because lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In this sense, our parameters are just intermediate between the typical solar wind values mentioned above and those in the upper solar corona, i.e., c/v Ai ∼ 10 2 and c/v Ae ∼ 3. Verscharen et al (2020) demonstrated that plasma models employing m i /m e = 100 and c/v Ai  10 can successfully cover physics on scales 0.2d i for β i ∼ β e ∼ 1, which is the regime we have explored here. Since we employ that exact value of m i /m e , an order of magnitude larger value of c/v Ai , and we also have c/v Ae  10, we are confident that our fully kinetic simulations provide quite a correct modeling of the plasma dynamics down to electron scales.…”
Section: Discussionmentioning
confidence: 77%
“…In this sense, our parameters are just intermediate between the typical solar wind values mentioned above and those in the upper solar corona, i.e., c/v Ai ∼ 10 2 and c/v Ae ∼ 3. Verscharen et al (2020) demonstrated that plasma models employing m i /m e = 100 and c/v Ai  10 can successfully cover physics on scales 0.2d i for β i ∼ β e ∼ 1, which is the regime we have explored here. Since we employ that exact value of m i /m e , an order of magnitude larger value of c/v Ai , and we also have c/v Ae  10, we are confident that our fully kinetic simulations provide quite a correct modeling of the plasma dynamics down to electron scales.…”
Section: Discussionmentioning
confidence: 77%
“…With these parameters, the simulated electrons are mildly relativistic, which they are not in the real solar wind. However, the effect of mildly relativistic electrons on the propagation and damping of kinetic-scale normal modes, including KAWs, Alfvén/ion-cyclotron (known as A/IC) waves and fast-magnetosonic/whistler (known as FM/W) waves, is negligible (Verscharen et al 2020) and not important for the evolution of the turbulent cascade, regardless of the processes that carry the cascade to subproton scales.…”
Section: Simulationmentioning
confidence: 99%
“…An important difference between the whistler and kinetic Alfvén simulations was that the mass ratio used in the latter was m i / m e = 100. One of the side effects of lower mass ratio, in the linear limit, is that the kinetic Alfvén waves can reach beyond electron scales for smaller mass ratio, but damp critically well before electron scales are reached for realistic mass ratios [91].…”
Section: Heating Profilementioning
confidence: 99%
“…These parameters are varied over a broad range of values. For example, in the linear theory calculations, Verscharen et al [91] studied 1 < m i /m e < 1836 and 10 -4 < v A /c < 1/3. In nonlinear PIC simulations Gary et al [56] studied 25 < m i /m e < 1836 and Hughes et al [93] studied 0.025 < vth , e /c < 0.10.…”
Section: Search For Control Parameters and Scaling Relationsmentioning
confidence: 99%
See 1 more Smart Citation